HUBUNGAN ANTARA PEMAHAMAN LITERASI DIGITAL DAN MODEL PEMBELAJARAN INKURI DENGAN KESIAPAN IMPLEMENTASI DEEP LEARNING PADA GURU PENDIDIKAN AGAMA KRISTEN DAN BUDI PEKERTI SD SE-KECAMATAN PANGURURAN TAHUN AJARAN 2025-2026 (Jurnal Pendidikan dan Bahasa Sastra Harapanan, 2026)
The national curriculum transition toward the Deep Learning paradigm demands teacher readiness in integrating technological proficiency and active learning methods; however, in practice, learning tendencies remain administrative and fixed at the "surface learning" level. This study aims to analyze the relationship between Digital Literacy Understanding (X1) and the Inquiry-Based Learning Model (X2), both partially and simultaneously, with Deep Learning Implementation Readiness (Y) among Christian Religious and Character Education (PAKBP) elementary school teachers in Pangururan District. Utilizing a quantitative correlation approach, data were collected through case-study-based thinking skills test instruments from the teacher population in Pangururan District and analyzed using multiple linear regression via SPSS 26. The findings indicate that Digital Literacy has a very strong, positive, and significant relationship (r = 0.769; Sig. < 0.01) and serves as the dominant predictor of teacher readiness (t count = 3.906). Conversely, the Inquiry Learning Model does not partially provide a significant contribution (Sig. 0.061 > 0.05), indicating that a standalone inquiry model without technological support is insufficient to drive readiness for the new curriculum. Simultaneously, both variables contribute a significant 64% to Deep Learning Implementation Readiness, while the remaining 36% is influenced by other external factors. This study concludes that techno-pedagogical integration (TPACK) through "Digitalized Inquiry" is an absolute prerequisite for PAKBP teachers to create meaningful, mindful, and joyful learning in the digital era.